Usefulness of nuclear morphometry and agNOR score in predicting radiation response in squamous cell cancer of the head and neck - Biswal, Biswa Mohan; Othman, Nor Hayati (2000)
Squamous cell cancers of the head and neck have diverse biological behavior and prediction of radiation response. There is lack of specific investigation tool to predict the subgroup of cancers unresponsive to radiotherapy. This is a prospective study in the use of nuclear and nucleolar morphometric parameters for the prediction of radiation response. Twenty six patients with squamous cell cancers of the head and neck region were recruited to receive a course of palliative radiation therapy to a dose of 30Gy in 10 fractions over 2 weeks. Fine needle aspiration cytology was performed on day 1 and day-5 of the above radiotherapy schedule. The AgNOR score and nuclear morphometric study was done using computerized image analyzer. A total of 26 patients were evaluable with a median age of 44 years (range 17-76 years). The primary tumors were from nasopharynx (11), larynx & hypopharynx (5), metastatic node (4), and miscellaneous tumors of head and neck (6). The response to radiation was gradual with a median regression time of 4 weeks.The mean AgNOR score was 3 dots/ nucleus (range (1.2-7dots/nucleus). The average nuclear diameter was 11.073J (range 7.70-16.6) and nucleolar diameter 2.92 (1.09-11.66). Patients with higher pretreatment AgNOR score (> 2.5) were associated with disease progression and metastasis. However patients whose cancer cells showed increase in the diameter of the nucleus after initial radiotherapy fared better with local control by radiotherapy than those cancer cells were not.